‘Am I That Name?’ - Riley, Denise. author. aut Link
VI, 126 p.
Keywords: Writing about changes in the notion of womanhood, Denise Riley examines, in the manner of Foucault, shifting historical constructions of the category of "women" in relation to other categories central to concepts of personhood: the soul, the mind, the body, nature, the social. Feminist movements, Riley argues, have had no choice but to play out this indeterminacy of women. This is made plain in their oscillations, since the 1790s, between concepts of equality and of difference. To fully recognize the ambiguity of the category of "women" is, she contends, a necessary condition for an effective feminist political philosophy.